Dietary supplementation with Bifidobacterium longum subsp. infantis (B. infantis) in healthy breastfed infants: study protocol for a randomised controlled trial. Issue 1 (December 2016) - Awasthi, Smita; Wilken, Reason; Patel, Forum; German, J.; Mills, David; Lebrilla, Carlito; Kim, Kyoungmi; Freeman, Samara; Smilowitz, Jennifer; Armstrong, April; Maverakis, Emanual
Abstract Background The development of probiotics as therapies to cure or prevent disease lags far behind that of other investigational medications. Rigorously designed phase I clinical trials are nearly non-existent in the field of probiotic research, which is a contributing factor to this disparity. As a consequence, how to appropriately dose probiotics to study their efficacy is unknown. Herein we propose a novel phase I ascending dose trial ofBifidobacterium longum subsp. infantis (B. infantis ) to identify the dose required to produce predominant gut colonisation in healthy breastfed infants at 6 weeks of age. Methods/design This is a parallel-group, placebo-controlled, randomised, double-blind ascending dose phase I clinical trial of dietary supplementation withB. infantis in healthy breastfed infants. The objective is to determine the pharmacologically effective dose (ED) ofB. infantis required to produce predominant (>50 %) gut colonisation in breastfed infants at 6 weeks of age. Successively enrolled infant groups will be randomised to receive two doses of eitherB. infantis or placebo on days 7 and 14 of life. Stool samples will be used to characterise the gut microbiota at increasing doses ofB. infantis . Discussion Probiotic supplementation has shown promising results for the treatment of a variety of ailments, but evidence-based dosing regimes are currently lacking. The ultimate goal of this trial is to establish a recommended starting dose ofB. infantis for further efficacy-testing phase II trials designed to evaluateB. infantis for the prevention of atopic dermatitis and food allergies in at-risk children. Trial registration Clinicaltrials.gov #NCT02286999, date of trial registration 23 October 2014.